Políticas de saúde brasileiras e pandemias modernas: uma análise dialética - Xerri, Bibiana Ignês Gasparini (My University, 2021)
The present study is an ending of course work, concerning a path of the public health policies in Brazil in relation to modern pandemics. The problem proposed for this work questions how adequate are the health attention models in their capability to answer modern pandemics. Its main objective is to analyse the current public health policy in its capability of answering modern pandemics. To understand this work?s study object, the dialectical materialistic method was used, highlighting the categories historicity, particularity, singularity and superstructural totality, besides the own dialectical cycle, of thesis, antithesis and synthesis. This monograph is an exploratory study anchored in a qualitative approach. The bibliographic and documental researches were used to collect data about the thema. Firstly, a rescue of the constitution of the brasilian public health policy was made, starting from a short overview of the emergence of public health policies in the global level. Then, what modern pandemics are was delimited and which were the global reactions, in terms of legislations and initiatives, to face them; then, a return to the brazilian context to identify this country's paradigm amongst the modern pandemics. Finally, the coverage of the current models of public health when addressing modern pandemics was analysed, how society is by them stricken and the political role of these crises of public health. It was verified that the way public health policies were implemented in Brazil privileges the interest of the capital, although the universalization attempts, because these were victims of the neoliberal offensive; the health system being progressively precarized, when struck by a pandemic, it shows itself as insufficient and evidences the discriminatory aspect professed by the politically conservative governments. There are possibilities of resistance, found mainly in territorialization of health initiatives and in the reorganization of management inside the health equipments and in the assistance programs instituted to furnish the population in this (and in other) periods. [resumo fornecido pelo autor]
O presente estudo é um trabalho de conclusão de curso, cujo tema trata de uma trajetória das políticas públicas de saúde no Brasil em relação às pandemias modernas. O problema proposto nesse trabalho questiona quão adequados são os modelos de atenção à saúde atuais em sua capacidade de resposta às pandemias modernas. Seu principal objetivo é analisar a política de saúde pública contemporânea em sua capacidade de responder às pandemias modernas. Para compreender o objeto de estudo do trabalho, foi utilizado o método materialista dialético, com destaque às categorias historicidade, particularidade, singularidade e totalidade da superestrutura, além do próprio ciclo dialético, de tese, antítese e síntese. Esta monografia é um estudo exploratório ancorado na abordagem de pesquisa qualitativa. Foram utilizadas as pesquisas bibliográfica e documental para a coleta de dados referentes à temática. Inicialmente, se fez um resgate da política pública de saúde brasileira em sua constituição, partindo de um breve panorama do surgimento das políticas públicas de saúde a nível global. Em seguida, foi delimitado o que são pandemias modernas e quais foram as reações globais, em termos de legislações e iniciativas, para fazer frente a elas; logo, se retornou ao contexto brasileiro para identificar o paradigma desse país em meio às pandemias modernas. Por fim, se analisou a abrangência dos atuais modelos de saúde pública quando tratando de pandemias modernas, como a sociedade é por elas atingidas e o papel político dessas crises de saúde pública. Verificou-se que o modo como as políticas públicas de saúde foram historicamente implantadas no Brasil privilegia os interesses do capital, apesar das tentativas de universalização, pois essas foram vitimadas pela ofensiva neoliberal; sendo o sistema de saúde progressivamente precarizado, ao ser atingido por uma pandemia se mostra insuficiente e evidencia o aspecto discriminatório preconizado pelos governos de orientação política conservadora. Há possibilidades de resistência, encontradas principalmente na territorialização das iniciativas em saúde e da reorganização da gestão dentro dos equipamentos de saúde e nos programas assistenciais instituídos para suprir a população nesse (e em outros) períodos. [resumo fornecido pelo autor]
Keywords: Política de saúde; Pandemias; Política pública